TNF rs1799964 as a Predictive Factor of Acute Toxicities in Chinese Rectal Cancer Patients Treated With Chemoradiotherapy. Issue 45 (November 2015) - Zhang, Hui; Wang, Mengyun; Shi, Tingyan; Shen, Lijun; Liang, Liping; Deng, Yun; Li, Guichao; Zhu, Ji; Wu, Yongxin; Fan, Ming; Deng, Weijuan; Wei, Qingyi; et al.
Abstract : Abstract: Acute toxicity is the main dose-limiting factor in the chemoradiotherapy of rectal cancer patients and depends on several pro-inflammatory factors, including interleukin-1 (IL-1), IL-6, and tumor necrosis factor-alpha (TNF-α). It is unknown whether genetic factors, such as single-nucleotide polymorphisms (SNPs) in the IL-1, IL-6, and TNF genes, are also associated with acute toxicity in the process. We genotyped 5 potentially functional SNPs in these 3 genes ( TNF rs1799964, TNF rs1800629, IL-6 rs1800796, and IL-1 rs1143623, IL-1 rs1143627) and estimated their associations with severe acute radiation injury (grade ≥2) in 356 rectal cancer patients. We found a predictive role of the TNF rs1799964 T variant allele in the development of acute injury (for CT vs CC: adjusted odds ratio [OR] = 4.718, 95% confidence interval [CI] = 1.152–19.328, P  = 0.031; for TT vs CC: adjusted OR = 4.443, 95% CI = 1.123–17.581, P  = 0.034). In the dominant model, for CT/TT vs CC, the adjusted OR = 4.132, 95% CI = 1.069–15.966, and P  = 0.04. Our results suggested that genetic variants in the TNF gene may influence acute injury in rectal cancer patients treated with chemoradiotherapy and may be a predictor for personalized treatment. Additional larger and independent studies are needed to confirm our findings.